PURWARUPA SISTEM PEMBUKA PINTU GERBANG DENGAN HANDPHONE BERBASIS ARDUINO UNO R3 VIA WIFI - , ADI SULISTIYANTO, Ariesta Martiningtyas H., S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The technology and information devolopment growing so fast nowday. Inthis time, The technology and information has become a necessity by the society. One of the implementation was opened the gate automatically. Most people get lazy when must go down to open the gate.. But with the development of technology and information, they invented a remote cotnrol by smartphone android applications. Mobile is a practical tool that can be taken anywhere, anywhen, bags and etc the some people already have it.. The system uses a wiffi with ethernet as controller of the system using an Arduino Uno.servo motors use to move the door (open and closed) and solenoid key as locked. The results show that the gates opening system successfully created and can work well as expected use router wifi that later can be applied to the actual gate so that without having to do it manually.